Mediastinal Lymphadenopathy- “Diagnostic Dilemma in Indian Subcontinent” A Review (Advancements in Homeopathic Research, 2022)
This review addresses invasive procedures for confirmatory staging of the mediastinum in patients with lung cancer. The focus is on patients in whom there is a strong suspicion of lung cancer. Such a presumptive clinical diagnosis is generally possible by an experienced clinician after an assessment of risk factors, and a review of the clinical presentation and the radiographic appearance on a CT scan. If the presence of distant metastatic disease has been ruled out, the status of the mediastinum becomes the crucial factor in selecting the optimal treatment strategy. The initial clinical evaluation (ie, clinical presentation and CT scan findings) already yields a presumptive clinical stage with respect to the mediastinum, which may have beensupplemented by a positron emission tomography (PET) scan as well. However, noninvasive imaging tests can provide only a suspicion that involvement of the mediastinal nodes is present or absent, and in many clinical situations confirmation of the status of these nodes by an invasive test is necessary.
Keywords: radiographic; CT scan; mediastinum; Diagnostic Dilemma